Evaluation of growth in diesel fuel and surfactants production ability by bacteria isolated from fuels in Costa Rica - Rodríguez Rodríguez, Carlos E. (2012)
A total of 149 bacterial strains previously isolated from fuels stored in Costa Rica were selected in terms of their ability to grow aerobically in diesel and produce bioemulsifier active compounds. The diesel growth was evaluated by a redox-indicator based test, and surfactant production was estimated indirectly by both the emulsification index determination (E24) and hemolytic activity. Twenty-six strains (16.8%) were considered as capable of growing in diesel, while surfactant production was detected in 22 (14.8%), estimated according to E24. Seven strains showed high production of biosurfactants (E24 ≥ 50%), headed by Pseudomonas aeruginosa 148D-O, P. aeruginosa 87R-B and Bacillus pumilus 133S-B. No significant correlation was observed between hemolytic patterns and growth outcomes in diesel or E24. Surfactant producing strains should be studied further to assess its potential applications.